On the Diagrammaticity of Ancient Texts and Its Importance for the History of Science: Based on the Example of the Early Chinese Mathematical Text The Gnomon of the Zhou. Issue 2 (1st June 2020) - Chemla 林力娜, Karine
Abstract: Even when ancient texts consist simply of discourse, they are available to historians through documents in which they are displayed with diagrammatic features (e.g., lines, columns, paragraphs, sections). Usually these diagrammatic features are not mentioned in critical editions, which often even reshape them. With the example of the Chinese mathematical canonical text The Gnomon of the Zhou, this article argues that these diagrammatic features sometimes give historians essential clues for tackling key issues. The author shows how taking these features into account might help when interpreting sentences that have never really been understood. The author argues that the interpretation of these sentences suggests a historical scenario for the production and dating of the text of The Gnomon of the Zhou . Interestingly, this scenario echoes what is indicated by the diagrammatic features of the recently excavated mathematical manuscripts. This scenario also is supported by the different types of knowledge in mathematics and the astral sciences that different parts of the text display. Finally, the argument suggests that the 1213 edition of The Gnomon of the Zhou was faithful to diagrammatic features of very ancient documents through which the text was handed down. The author provides evidence that shows eighteenth-century philologist Dai Zhen seemed to have understood this point.